Study of Ground Vibration Generated by Train at Rail Curve - Nicholas, Brian MClair; Ling, Felix Ngee Leh (Recent Trends in Civil Engineering and Built Environment, 2024)
A train is a type of rail transportation that consists of a group of connected vehicles that convey passengers or cargo along a railroad track. However, ground vibration produced by the train for some cases can be disturb the comfort of residents who live in a nearby area. There is a concern that the curve railway could generate higher level of ground vibration due to centrifugal force of the train movement to maneuver the curve. Hence it is necessary to carry out the study for the evaluation of train-induce ground vibration. This case study aimed to determine the ground vibration level of train at rail curve and compared it with straight rail. The finding of this study was aimed to assess the effect of rail geometry on the ground vibration and the evaluation of the effect of train-induced ground vibration towards nearby residential area. The location of the case study was selected on along the KluangGemas railway. Three accelerometer sensors for each Location 1 and Location 2 were set on straight and curve railways. For the soil investigation, Mackintosh Probe Test was carried out to know the bearing capacity of the soil. The ground vibration data obtained was evaluated using DOE (Department of Environment) guideline to make sure it is safe for residential nearby. The level of ground vibration of train at rail curve was obtained and it is known that the ground vibration at rail curve has a higher peak velocity compared to a straight rail. Hence, for future improvements, an additional Mackintosh probe test can be performed on different location to obtain more accurate result if the distance for both Location 1 and 2 are too far.